Communism. ([Australia] : [publisher not identified], 1925)
Newspaper cuttings from the Australian press clippings collection on Communism in Australia mostly condemning the Communist Party in Australia. There are also several leaflets and pamphlets (both pro and anti communism).
Includes articles from the period 1925 to 1957.
Keywords: Communist Party of Australia -- History; Communism -- Australia -- History -- 20th century; Communists -- Australia -- History -- 20th century; Anti-communist movements ( -- Australia -- History -- 20th century; Clippings (Books, newspapers, etc.); Australia -- Politics and government -- 20th century; Australian